2010
DOI: 10.3791/2435
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Motility Monitor (GIMM)

Abstract: The Gastrointestinal Motility Monitor (GIMM; Catamount Research and Development; St. Albans, VT) is an in vitro system that monitors propulsive motility in isolated segments of guinea pig distal colon. The complete system consists of a computer, video camera, illuminated organ bath, peristaltic and heated water bath circulating pumps, and custom GIMM software to record and analyze data. Compared with traditional methods of monitoring colonic peristalsis, the GIMM system allows for continuous, quantitative eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 16 publications
0
42
0
Order By: Relevance
“…Spatiotemporal maps made from these video records are designed to represent the movement of the whole segment as described above. In contrast, in the mid-to distal colon where the contents are more solid, activity is initiated by insertion of a fecal pellet (epoxy coated natural pellet or artificial pellet) and spatiotemporal maps are designed to reflect the movement of the pellet through the colon as illustrated in the JOVE article of Hoffman et al 13 . Thus the setup of the experiment and analysis are crucial and depend upon the type of stimulus and the region being studied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spatiotemporal maps made from these video records are designed to represent the movement of the whole segment as described above. In contrast, in the mid-to distal colon where the contents are more solid, activity is initiated by insertion of a fecal pellet (epoxy coated natural pellet or artificial pellet) and spatiotemporal maps are designed to reflect the movement of the pellet through the colon as illustrated in the JOVE article of Hoffman et al 13 . Thus the setup of the experiment and analysis are crucial and depend upon the type of stimulus and the region being studied.…”
Section: Discussionmentioning
confidence: 99%
“…While many groups have generated their own software packages or plugins, they all analyze diameters of a tissue segment and convert those various diameters to grayscale representation. A commercially available recording and analysis system called the GastroIntestinal Motility Monitoring system (GIMM) provides a turnkey approach that allows for analysis of both propulsive motility via fecal pellet velocity determination in the guinea pig distal colon 13 as well as analysis of propulsive and mixing motility patterns with a fluid stimulus in intact intestinal segments 4,5,[14][15][16][17][18][19] 4. General Experimental Procedures 1.…”
Section: Introductionmentioning
confidence: 99%
“…Studies recommend not pinning the organ until it is completely taut, as this inhibits contraction. 49,69 However, since the program analyses a cross-section and measures the change in diameter, if there is too much movement it could be analyzing instead the oscillation of adjacent cross-sections of the organ. A possible method to include this would be installing a tracking system where movement of the organ could be monitored, and negated during analysis.…”
Section: Effect Of Anticholinergic Drugs On Slow Wave Motilitymentioning
confidence: 99%
“…It was suggested that for analysis, the settings were adjusted to high contrast between the organ and background. 49 This required heightening the contrast, and increasing the exposure and brightness. Any markings or debris within the camera viewfinder would create artifacts and noise in the spatiotemporal map.…”
Section: Gimm Organ Bath Systemmentioning
confidence: 99%
See 1 more Smart Citation